Pola Distribusi Klorofil-a dan Total Suspended Solid (TSS) di Teluk Toli Toli, Sulawesi - Anindya Wirasatriya (Buletin Oseanografi Marina, 2011)
Abstract The aim of this research is to investigate the distribution pattern of chlorophyl a and total suspended solid (TSS) at Toli toli Bay. The research was conducted in May 2009 by using research vessel Baruna Jaya VIII at 11 sampling stations in Toli toli Bay. Based on the distribution patterns of chlorophyll a, Toli toli Bay is categorized in good condition. Chlorophyll a concentrations were about 2.43 mg/m3 and ranged from 0.6-6.14 mg/m3. Horizontally, high chlorophyll a distribution were found in areas near estuary and reduced toward the open ocean. Vertically, the maximum chlorophyll a concentration was found in 25 m depth and then decreased until 100 m depth. TSS concentrations were about 7.65 mg/l and ranged from 5.8-10.4 mg/l which is still under the quality standard of the Ministry of Environment.   KeyWords    : Chlorophyl a, Total suspended solid (TSS), Toli toil, Sulawesi